Application of photodynamic activation of prodrugs combined with phototherapy in tumor treatment - Yining Du; Jingyuan Zhao; Shuai Li; Hong Yuan (Molecular Cancer)
Abstract The design of prodrugs aims to address the issues of systemic toxicity and poor specificity associated with traditional chemotherapy drugs, thereby improving patient survival rates. However, effectively controlling the activation of prodrugs and further improve the efficacy remains a significant challenge that needs to be addressed. Photodynamic therapy (PDT) is a non-invasive cancer treatment that utilizes photosensitizers (PS) to generate reactive oxygen species (ROS) under light irradiation, selectively killing tumor cells, but PDT still faces challenges such as limited therapeutic efficacy. To address challenge in cancer treatment, light-activated prodrugs have emerged as a promising strategy to achieve precise drug release and activation through light control in terms of time and location. This review explores the classification and mechanisms of light-activated prodrugs, with a focus on covalent and non-covalent photosensitizer-drug conjugates. These approaches enhance targeting, precisely control drug release, and achieve synergistic effects between PDT and chemotherapy. By analyzing these strategies, we highlight their potential in improving PDT efficacy and advancing targeted cancer therapy. Finally, we discuss future directions for designing advanced light-activated prodrug systems, providing new insights for the development of more effective and targeted cancer treatments.